Des entreprises dans les salles de classe ? La révolution conservatrice des grandes écoles d'ingénieurs - Adrien Delespierre (Les éditions de la Maison des sciences de l'Homme, 2015)
Since the 1980's, French grandes écoles are under critics announcing the end of a declining educational model, which is condemned to disappear or to adapt itself to requirements of "globalization". In order to integrate new criteria of excellence, French engineering schools reform their pattern of selection and education, which is traditionally founded on academic values. Taking for object training programs of a few engineering schools (l'École polytechnique, l'École centrale, l'ENSTA-Bretagne et AgroSup Dijon), this article interrogates the diffusion of new forms of managerial knowledges and educational technics: to what extent are they modifying hierarchy between disciplines in these schools? Do they represent a breaking in school's educational traditions, and do they modify previous symbolic order? We analyze educational strategies in link with history and specific position of each school into French field, and try to demonstrate that, despite of evolutions modifying French elite's training, principles of hierarchical organization ruling grandes écoles's universe are not overturned.